Chapter Renewable power sources in coastal areas. A viability assessment in the scope of needs and regulations - Bono, Andrea (Proceedings e report, 2020)
The work deals with renewable energy project, in the context of the deregulated energy market. Special attention is focused on renewables and on the situation in Italy from the standards point of view. The set up of a wind farm and a PV plant in coastal Sardinian area for both electricity and desalinated water production is studied. The convenience of fuelling desalination plants through renewables is investigated by taking into account additional on-side trading instruments. A model to simulate the operation wind and PV systems is applied both to calculate the produced energy and to assess the performance of a desalination plant, namely a reverse osmosis plant driven with PV and wind sources that works in a small island site.